Deteksi Escherichia coli Resisten Antibiotik pada Sumber Air dari Lingkungan Peternakan Unggas di Kecamatan Kelapa Lima Kota Kupang” - Annisah Lis Dewi; Novalino H.G Kallau; Annytha I.R Detha (Jurnal Veteriner Nusantara, 2023)
Clean water is water that can be used for daily purposes whose quality meets health requirements and can be drunk if it has been cooked. The source of origin of the spread of resistant bacteria in addition to human and environmental origin has been reported to also come from animal husbandry. The presence of antibiotic-resistant bacteria such as Escherichia coli on farms is a threat to the health of farm animals and humans around the farm area. This studyaims to obtain information about the percentage of E. coli and the incidence of antibiotic resistance in E. coli bacteria isolated from water sources in the poultry farming environment in Kelapa Lima District, Kupang City. A total of 30 water source samples were taken by purposive sampling method, out of 30 samples 16 positive samples of E. coli were found. Samples are tested to obtain E. coli isolates supported by identification test examinations with biochemical tests and subsequently tested their sensitivity patterns to antibiots. The study was conducted by the Kirby-Bauer method. The type of antibiotic used in this study is based on the type of antibiotic in EFSA (2012) used in the monitoring of Resistant Antimicrobials (AMR) for Salmonella spp and E. coli through food. This guide suggests using a class of antibiotics commonly used in the treatment of bacterial infections in animals as well as humans. The interpretation of the results of this sensitivity test refers to the Clinical and Laboratory Standards Institute (CLSI 2012). The results of this study showed that as much as 53.3% (16/30 samples) of the water population in the poultry farming environment in Kelapa Lima District, Kupang City contained E. coli and obtained a percentage of E. coli that was resistant to tetracycline antibiotics, which was 6.25% (1/16 sample).